Strategic Risk Management of Digital Transformation in the Economic Security of Industrial Enterprises - Ivanov, Mihail; Martseniuk, Larysa; Angelova, Miglena; Faifer, Serhii (Dr. Viktor Koval, 2025)
Introduction. Digital transformation has become a determinant factor influencing enterprises’ economic security, especially during crises and global concurrences. Despite its numerous advantages, digitalisation poses new risks, such as cyber threats, regulatory instability, and information leaks. Digitalisation as an infrastructure for innovation has become a strategic priority, primarily through the extension of digital government services, cloud resolutions, and metadata analytical tools to support the economic development of industry enterprises. Aim and tasks. This study aims to develop an integrated system of strategic risk management for digital transformation in industry enterprises’ economic security to minimise economic losses, increase adaptiveness to digital changes, and eliminate risks in industry enterprises’ economic security. Results. This study analyses modern approaches to ensuring economic security: systemic, risk-oriented, resource-oriented, and integrated approaches. The analysis revealed that only 25.6% of IT enterprises utilise Big Data analytics, while 7.1% employ AI technologies, highlighting the substantial untapped potential for further digital transformation. This study developed a structural model of a digital economic security management platform, including risk analytics, threat management, cyber protection, monitoring, and reporting. A formalised risk estimation model was built, considering financial, operational, and external factors. An integrated approach is suggested to build a digital platform for the management of enterprises’ economic security, which combines risk-oriented methods, cyber-protection, and big data analytics. Conclusions. This study proposes an approach for digital transformation in economic security management, featuring module architecture to monitor, forecast, and respond to threats. It presents formalised module architecture and a platform structural model for economic security monitoring, comprising four subsystems: financial, operational, risk-oriented, and external factors. The model enables rational resource allocation, threat forecasting, and adaptive decision-making in post-conflict scenarios. Enterprise digital transformation in strategic management and economic security is a key requirement for restoring, strengthening, and safeguarding the national interest.